Health promotion in German kindergartens—design and methods of the exploratory, cluster-randomized, mixed methods KNEIPP–KITA Bavaria study - Ortiz, Miriam; Bernardi, Christine; Welker, Christine; Boyer, Lisa; von Sommoggy, Julia; Baurecht, Hansjoerg; Roll, Stephanie; Tissen-Diabaté, Tatjana; Herrmann, Anne; Brinkhaus, Benno (Frontiers in Medicine, 2025)
BackgroundThe Kneipp Health Concept, which can be traced back to the German Sebastian Kneipp, integrates five health-promoting elements: physical activity, healthy nutrition, medicinal herbs, mental wellbeing and hydrotherapy. This concept is embedded in a pedagogical framework for children and has been adopted by more than 500 kindergartens across Germany and in other countries. The KNEIPP–KITA study Bavaria aims to evaluate the short- and medium-term effects of KHC on the health and wellbeing of children, their parents, and educational staff.MethodsThis explorative, cluster-randomized, matched-pair, two-arm controlled, mixed-methods study is being conducted in 10 kindergartens, which are randomly assigned to either the Kneipp group (implementing the Kneipp Health Concept as intervention) or a control group. Children aged 3 years and older, their parents, and kindergarten staff are included in the study, with a follow-up period of 24 months. Staff in the Kneipp group receive a specific training in the five elements of Kneipp Health Concept, after which they integrate these components into daily routine of their kindergarten. The control group continues their usual activities without implementing the Kneipp Health Concept. Outcome parameters (assessed through questionnaires in children, parents and staff) include health status, health consciousness, health-related behavior, family health, and quality of life at 9, 15, and 21 months after the Kneipp Health Concept training (start of intervention). In addition, barriers and facilitators of the implementation are explored in a qualitative sub-study through semi-structured interviews conducted with kindergarten staff and parents in the Kneipp group at baseline and 14–16 months post-training. Data analyses will be carried out at both the individual and cluster level, with separate analyses for children, parents, and staff. The qualitative data will be analyzed using the Framework Method following the approach outlined by Gale et al.DiscussionThe results of the study pave the way for a sustainable implementation of the Kneipp Health Concept. In addition, this exploratory study will inform the planning of future intervention studies with valuable data material and contribute to the development and evaluation of effective childhood prevention strategies.Trial registrationDeutsches Register Klinischer Studien DRKS (German clinical trials register) ID: DRKS00031865.